Hyperacute Incidental Late Myocardial Enhancement in Ischemic Stroke Using Chest Spectral CT: Relationship with Etiology - Rodriguez Granillo, Gaston Alfredo (2022)
Background: Hyperacute cardiac imaging of patients with acute ischemic stroke (AIS), though desirable, is impractical. Using delayed-enhancement, low-dose, non-gated, chest spectral computed tomography scans (DESCT), we explored the prevalence and patterns of incidental myocardial late iodine enhancement (LIE) and embolic sources, and their relationship with stroke etiology. Methods: Since July 2020, DESCT was performed after cerebrovascular CT angiography (CTA) among patients with suspected AIS undergoing CT using a dual-layer spectral scanner, without additional contrast administration. Images were analyzed using monoenergetic reconstructions and iodine density maps, and the myocardial extracellular volume fraction (ECV, %) was calculated. Results: Eighty patients with AIS were included. DESCT identified a cardiac thrombi in 6 patients (7.5%), and a complex aortic plaque in 4 (5%) cases; reclassifying 5 embolic strokes of uncertain source (28% of ESUS) to cardioembolic (CE, n = 3) and non-CE (n = 2) etiologies. LIE was identified in 38 (48%) patients, most commonly (82%) of ischemic pattern. We did not identify significant relationships between AIS etiology and the presence, pattern, and extent of LIE (p > 0.05); ECV (p = 0.56), severe aortic (p = 0.25) or valvular (p = 0.26) disease, or the extent of coronary calcification (p = 0.39). Patients with evidence of major cardiovascular DESCT findings had higher rates of all-cause death at 90 days (42% vs. 19%, p = 0.037). Conclusions: In this study, hyperacute cardiac imaging of AIS with DESCT identified a high prevalence of incidental cardiac disease predominantly involving LIE of ischemic etiology and mostly not related to the stroke etiology.